(untitled) (American International Journal of Business and Management Studies, 2019)
This analysis was carried out on the title of “Transforming Workers to Winners by Creating the High Performance Organizations”. The main aim of this article was to identify the factors that determine the continuous success of high performance organization. Then to get this objective the paper was organized into introduction, body & conclusion of the reviewed empirical data. Accordingly the empirical data was assessed and finally the conclusions drawn to show directions for business organizations how to make winners their employees.